Peran Strategis Internal Audit dalam Meningkatkan Tata Kelola Perusahaan: Studi kasus pada Perusahaan Sektor Keuangan - Titin Nur Azizah; Putri Ayu Evitasari; Irda Agustin Kustiwi (FEB Universitas Maritim Semarang, 2024)
This study reveals how internal audit can be a valuable asset in ensuring regulatory compliance, mitigating risk, and improving operational efficiency. Using qualitative research methodology and in-depth case studies, this research identifies internal audit best practices that can be implemented by financial sector companies. The study results show that internal audit has a strategic role in providing confidence to the board of directors and external stakeholders regarding corporate governance. Internal audit is not only a compliance checker, but also a strategic partner who provides recommendations for improving processes and policies. This research highlights the importance of coordination between internal audit, risk management and compliance to achieve common goals in improving corporate governance. Apart from that, this article also emphasizes the need to adopt audit technology and data analysis as an effort to more effectively support decision making. Thus, this research provides an in-depth look at how internal audit can play a strategic role in improving corporate governance, providing valuable insights for practitioners, researchers and stakeholders in the financial sector and related industries.